Index-based impact monitoring of water infrastructures in climate change mitigation projects: A case study of MGNREGA-IWMP projects in Maharashtra - Nalgire, Shivanand; Chinnasamy, Pennan (Frontiers in Water, 2022)
Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) is currently the largest funded rural development program in India to ensure rural livelihood by providing employment through different activities. Owing to climate change impacts and water scarcity, over a period of last five years, approximately more than 70% of activities (budget of 5 Billion USD per year) are focused on water issues. For better utilization of resources, MGNREGA has been implementing these works in convergence with many other schemes like Integrated Watershed Management Programme (IWMP) with the aim of restoring the rural natural resources like soil, vegetation, and water. Even though the largest Rural Development scheme in India, the Monitoring and Evaluation (M&E) does not focus on the actual impact on water resources, rather just focus on amount spent monitoring. This can lead to only funds spent but not much impact on water resources and earmarking data for monitoring. The recent advancements in remote sensing techniques have provided open access to high-resolution satellite data along with the processing platform. Considering the available technologies and gaps in the existing M&E framework, the current study developed low-cost, comprehensive, robust, and near real-time M&E framework to assess the impact of water projects. A novel Remote Sensing based Ecological Index (RSEI) has been developed to assess the overall ecological status of land surfaces due to the water infrastructures developed. The performance of RSEI has also been assessed using the secondary data of crop production in the region, which shows excellent results (adjusted R-square value of 82% and Pearson correlation coefficient of 0.92). In addition, RSEI results were compared against results of Government audits (e.g.by Comptroller Auditor General of India), wherein RSEI found similar areas of increased water status and crop productivity. Results indicate that the use of RSEI based M&E framework will allow for impact assessment of water infrastructure and also aid to identify the priority areas demanding an immediate intervention. Thus RSEI can be used as a decision support system for stakeholders including for smooth planning, designing, implementation, monitoring, and evaluation of water infrastructure for combating climate change extremes such as droughts.